Electron-stimulated purification of platinum nanostructures grown via focused electron beam induced deposition - Lewis, Brett B.; Stanford, Michael G.; Fowlkes, Jason D.; Lester, Kevin; Plank, Harald; Rack, Philip D. (Beilstein Journal of Nanotechnology, 2015)
Platinum–carbon nanostructures deposited via electron beam induced deposition from MeCpPt(IV)Me3 are purified during a post-deposition electron exposure treatment in a localized oxygen ambient at room temperature. Time-dependent studies demonstrate that the process occurs from the top–down. Electron beam energy and current studies demonstrate that the process is controlled by a confluence of the electron energy loss and oxygen concentration. Furthermore, the experimental results are modeled as a 2nd order reaction which is dependent on both the electron energy loss density and the oxygen concentration. In addition to purification, the post-deposition electron stimulated oxygen purification process enhances the resolution of the EBID process due to the isotropic carbon removal from the as-deposited materials which produces high-fidelity shape retention.
Keywords: beam induced processing; direct-write; electron beam induced deposition; nano

(untitled) - Botman, A.; Mulders, J. J. L.; Hagen, C. W. (Nanotechnology, 2009)

(untitled) - Huth, M.; Porrati, F.; Schwalb, C.; Winhold, M.; Sachser, R.; Dukic, M.; Adams, J.; Fantner, G. (Beilstein J. Nanotechnol., 2012)

Nanofabrication Using Focused Ion and Electron Beams: Principles and Applications - Utke, I.; Moshkalev, S.; Russell, P. (Oxford University Press, 2012)

(untitled) - Klein, K. L.; Randolph, S. J.; Fowlkes, J. D.; Allard, L. F.; Meyer, H. M., III; Simpson, M. L.; Rack, P. D. (Nanotechnology, 2008)

(untitled) - Fernández-Pacheco, A.; De Teresa, J. M.; Córdoba, R.; Ibarra, M. R. (J. Phys. D: Appl. Phys., 2009)

(untitled) - Brintlinger, T.; Fuhrer, M. S.; Melngailis, J.; Utke, I.; Bret, T.; Perentes, A.; Hoffmann, P.; Abourida, M.; Doppelt, P. (J. Vac. Sci. Technol., B, 2005)

(untitled) - Rykaczewski, K.; White, W. B.; Fedorov, A. G. (J. Appl. Phys., 2007)

(untitled) - Riazanova, A. V.; Costanzi, B. N.; Aristov, A.; Rikers, Y. G. M.; Ström, V.; Mulders, J. J. L.; Kabashin, A. V.; Dan Dahlberg, E.; Belova, L. M. (Nanotechnology, 2014)

(untitled) - Mehendale, S.; Mulders, J. J. L.; Trompenaars, P. H. F. (Nanotechnology, 2013)

(untitled) - Toth, M.; Lobo, C. J.; Hartigan, G.; Ralph Knowles, W. (J. Appl. Phys., 2007)

(untitled) - Roberts, N. A.; Magel, G. A.; Hartfield, C. D.; Moore, T. M.; Fowlkes, J. D.; Rack, P. D. (J. Vac. Sci. Technol., A, 2012)

(untitled) - Roberts, N. A.; Fowlkes, J. D.; Magel, G. A.; Rack, P. D. (Nanoscale, 2013)

(untitled) - Nicholas, A. R.; Carlos, M. G.; Jason, D. F.; Philip, D. R. (Nanotechnology, 2013)

(untitled) - Graells, S.; Alcubilla, R.; Badenes, G.; Quidant, R. (Appl. Phys. Lett., 2007)

(untitled) - Stanford, M. G.; Lewis, B. B.; Noh, J. H.; Fowlkes, J. D.; Roberts, N. A.; Plank, H.; Rack, P. D. (ACS Appl. Mater. Interfaces, 2014)

(untitled) - Plank, H.; Noh, J. H.; Fowlkes, J. D.; Lester, K.; Lewis, B. B.; Rack, P. D. (ACS Appl. Mater. Interfaces, 2014)

(untitled) - Porrati, F.; Sachser, R.; Schwalb, C. H.; Frangakis, A. S.; Huth, M. (J. Appl. Phys., 2011)

(untitled) - Sachser, R.; Reith, H.; Huzel, D.; Winhold, M.; Huth, M. (ACS Appl. Mater. Interfaces, 2014)

(untitled) - Mackus, A. J. M.; Thissen, N. F. W.; Mulders, J. J. L.; Trompenaars, P. H. F.; Verheijen, M. A.; Bol, A. A.; Kessels, W. M. M. (J. Phys. Chem. C, 2013)

(untitled) - Geier, B.; Gspan, C.; Winkler, R.; Schmied, R.; Fowlkes, J. D.; Fitzek, H.; Rauch, S.; Rattenberger, J.; Rack, P. D.; Plank, H. (J. Phys. Chem. C, 2014)

(untitled) - Noh, J. H.; Stanford, M. G.; Lewis, B. B.; Fowlkes, J. D.; Plank, H.; Rack, P. D. (Appl. Phys. A, 2014)

(untitled) - Hopf, C.; Schlüter, M.; Schwarz-Selinger, T.; von Toussaint, U.; Jacob, W. (New J. Phys., 2008)

(untitled) - Mackus, A. J. M.; Leick, N.; Baker, L.; Kessels, W. M. M. (Chem. Mater., 2012)

(untitled) - van Dorp, W. F.; Wnuk, J. D.; Gorham, J. M.; Fairbrother, D. H.; Madey, T. E.; Hagen, C. W. (J. Appl. Phys., 2009)

(untitled) - Arnold, G.; Timilsina, R.; Fowlkes, J.; Orthacker, A.; Kothleitner, G.; Rack, P. D.; Plank, H. (ACS Appl. Mater. Interfaces, 2014)

(untitled) - Winkler, R.; Fowlkes, J.; Szkudlarek, A.; Utke, I.; Rack, P. D.; Plank, H. (ACS Appl. Mater. Interfaces, 2014)

(untitled) - Smith, D. A.; Fowlkes, J. D.; Rack, P. D. (Nanotechnology, 2008)